Por uma política pública a partir do pública da política : um estudo sobre banheiros na Orla da Lagoa da Pampulha sob a perspectiva dos direitos humanos - Fernanda Deister Moreira (2021)
Public toilets are essential infrastructure to guarantee the right to sanitation in public spaces and the right to inclusive and sustainable cities. Besides, the offer of restrooms encourages tourism, leisure, and social life. However, it is a challenge for the public authorities to offer these services that are frequently targeted at vandalism, drug use, and sex in public. Thus, the provision of these services requires constant maintenance and surveillance. Given this problem, this research aims to understand the perspective of supply and demand for public restrooms on the Pampulha Lake Shore (PLS) in Belo Horizonte, considered a UNESCO Cultural Heritage Site and a relevant public tourist space for the municipality. Observations and semi-structured interviews were conducted with passers-by and PLS street vendors and semi-structured interviews with representatives of the municipal government. The field data were analyzed using the Content Analysis technique and discussed in six categories for passers-by (availability, accessibility, health, quality and safety, conflicting choices, and affordability) and two for managers (accountability and adversities). To complement the field, comments on PLS toilets were used as a secondary database, which was present in Google Local Guides and was analyzed according to the Collective Subject Discourse technique in order to understand the collective opinion expressed in the virtual environment. In interviews with passers-by, greater depth was obtained in the issues of availability, accessibility, quality and safety, and affordability, as these are issues to be solved at PLS, also recognized by the public authorities. It was evident, both from the literature review, but confirmed by the data in the field, that the lack of this infrastructure has several consequences, mainly for women and girls, the elderly and people with disabilities, transgender people, street workers, and homeless people. Public managers presented several challenges in the conservation and maintenance of toilets in public spaces, reaffirming what was found in the literature review. It is interpreted that due to these challenges, many municipalities do not guarantee the provision of toilets in public places or do not take them as a priority. This is due to the lack of materialization of public policies in laws, standards, or guidelines that provide for ownership service, supply, and maintenance guidelines, among other aspects.